Art, Design and Communication Theory in Creating the Communicative Social Robot ‘Haru’ - Sandry, Eleanor; Gomez, Randy; Nakamura, Keisuke (Frontiers in Robotics and AI, 2021)
Haru is a social affective robot platform designed to support a wide range of research into human-robot communication. This article analyses the design process for Haru beta, identifying how both visual and performance art was an essential part of that process, and drawing out ideas of Haru’s communication as a science and as an art. Initially, the article examines how a modified form of Design Thinking shaped the work of the interdisciplinary development team—including animators, performers and sketch artists working alongside roboticists—to frame Haru’s interaction style in line with sociopsychological and cybernetic-semiotic communication theory. As the article explains, from these perspectives on communication any development process will tend to focus on creating a robot that is persuasive and able to transmit precise information clearly. The article moves on to highlight two alternative perspectives on communication, based on phenomenological and sociocultural theories, from which such a robot can be further developed as a more flexible and dynamic communicative agent. The various theoretical perspectives introduced are brought together by considering communication across three elements: encounter, story and dance. Finally, the article explores the potential of Haru as a research platform for human-robot communication across various scenarios designed to investigate how to support long-term interactions between humans and robots in different contexts. In particular, it gives an overview of plans for humanities-based, qualitative research with Haru.